The Effect of Solvency, Profitability, and Working Capital on Firm Value: Case Studies on Industrial Companies in IDX 2015-2019 - Andini Nurwulandari (GoAcademica Research & Publishing, 2020)
The publication of the financial statements (issuers) of the company is a time waiting for investors in the capital market, as investors will find out the progress of issuance, as a consideration for purchasing or selling their own shares, when publishing these financial reporting statements. This research uses quantitative techniques with descriptive interpretation. Data sources include company-owned financial data reports collected from the IDX and published online, as well as conducting library analysis by collecting data from the writing of related books and journals. The type of data used in the study is secondary data from 2015-2019 which was collected through a purposive sampling process. Statistical Descriptive Analysis and Mulicollinearity Test. From this research, it can be seen that the rate of working capital turnover, solvency and capital structure affect firm value, while profitability does not affect firm value.